2016
DOI: 10.1002/wsb.643
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal movements of greater sage-grouse populations in Utah: Implications for species conservation

Abstract: Greater sage-grouse (Centrocercus urophasianus; sage-grouse) is considered an umbrella species for sagebrush (Artemisia spp.) landscapes in western North America. In 2015, the U.S. Fish and Wildlife Service determined sage-grouse unwarranted for protection under the Endangered Species Act (1973) because of conservation actions in priority areas. Understanding seasonal movements is key to delineation and assessment of priority conservation areas. We monitored radiomarked sage-grouse from 1998 to 2013 throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 42 publications
(68 reference statements)
2
54
1
Order By: Relevance
“…He argued that increasing habitat quality does not necessarily lead to an increase in total population or densities, but increasing usable space can increase total population. Management actions implemented to remove or reduce PJ in areas where the sagebrush understory still provides potentially available habitat may increase the amount of useable space available for sage‐grouse, which could lead to increased local populations in areas where sagebrush habitat is a limiting factor (Dahlgren et al ).…”
Section: Discussionmentioning
confidence: 99%
“…He argued that increasing habitat quality does not necessarily lead to an increase in total population or densities, but increasing usable space can increase total population. Management actions implemented to remove or reduce PJ in areas where the sagebrush understory still provides potentially available habitat may increase the amount of useable space available for sage‐grouse, which could lead to increased local populations in areas where sagebrush habitat is a limiting factor (Dahlgren et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Sage-grouse population declines have been attributed to poor nest success (Taylor et al 2012), and Dahlgren et al (2016b) suggested the reproductive potential of smaller, more remote sage-grouse populations in Utah is limited by available habitat. Nest success for all years and cohorts on Anthro Mountain (0.43) was lower than nest success averaged over 14 sage-grouse studies (47.4%; Crawford et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…, Dahlgren et al. ). The 41 population boundaries were largely based on floristic characteristics (Miller and Eddleman ), presence of active leks, topography (barriers), and spatial separation (Connelly et al.…”
Section: Methodsmentioning
confidence: 99%
“…These include, but are not limited to, priority areas for conservation (PACs; USFWS 2013), 41 population boundaries (five of which are subdivided into 24 subpopulations) and seven management zones (Connelly et al 2004). Priority areas for conservations are largely based on known active lek locations and the distribution of sagebrush habitat but sometimes accounted for interseasonal habitat movements (Fedy et al 2012, Dahlgren et al 2016). The 41 population boundaries were largely based on floristic characteristics (Miller and Eddleman 2001), presence of active leks, topography (barriers), and spatial separation (Connelly et al 2004: Table 6.16).…”
Section: Cluster-level Assessmentmentioning
confidence: 99%